A comparison of physical comorbidities in patients with posttraumatic stress disorder developed after a terrorist attack or other traumatic event. Issue 5 (8th January 2019) - Ferretti, Fabio; Pozza, Andrea; Bossini, Letizia; Del Matto, Laura; Desantis, Serena; Olivola, Miriam; Gualtieri, Giacomo; Coluccia, Anna; Fagiolini, Andrea
Abstract: No study investigated whether the presence of specific medical comorbidities is associated with the type of traumatic event, in particular with terrorist attack (TA). In a group of subjects with posttraumatic stress disorder (PTSD), the current study investigated the association between the types of traumatic event (TA vs. other traumatic event [OTE]) and medical comorbidities, controlling for sex and PTSD duration. The Mini International Neuropsychiatric Interview, the Clinician‐Administered PTSD Scale, and the Davidson Trauma Scale were administered to 84 subjects diagnosed with PTSD. Thirty‐nine were victims of TA and 45 victims of OTE. TA was associated with higher prevalence of neoplasms ( β  = 2.60, p  = 0.02). Females were more protected than males from circulatory system comorbidities ( β  = 1.47, p  = 0.04), while PTSD duration was associated with higher prevalence of such comorbidities ( β  = 0.005, p  = 0.01). Females showed a higher prevalence of neoplasms than males ( β  = 2.50, p  = 0.02). Female sex was protective against metabolic syndrome ( β = −1.79, p  = 0.02). Patients with PTSD due to TA and female patients should be considered for their higher prevalence of neoplasms, while male patients and those with higher symptom duration should be monitored for circulatory disease and metabolic syndrome. Symptom duration might be associated with circulatory and metabolic disease. Implications for tailored and timely psychopharmacological and psychotherapeutic intervention for PTSD are discussed focusing on these specific medical comorbidities.